Risk of self-harm ideation in mothers of children with orofacial cleft defects: the Japan environment and children's study - Tsuchiya, Shinobu; Tsuchiya, Masahiro; Momma, Haruki; Igarashi, Kaoru; Nagatomi, Ryoichi; Saito, Masatoshi; Arima, Takahiro; Yaegashi, Nobuo; , the Japan Environment; Children’s Study; Kamijima, Michihiro; Yamazaki, Shin; et al. (Frontiers in Global Women's Health, 2024)
IntroductionCleft lip and/or palate (CL/P), the most prevalent congenital anomaly, has been associated with higher rates of child maltreatment. In particular, the presence of cleft lip has more of an impact on external appearance and may increase the risks of negative health outcomes such as parental postpartum depression; however, this concept remains controversial. Item #10 of the Edinburgh Postpartum Depression Scale is the assessment of parental self-harm ideation, and its presence in postpartum mothers merits risk assessments as an emergent issue that may affect the health of both mothers and infants. This study focused on the impact of CL/P on maternal self-harm ideation.MethodsOf 100,300 live births from a nationwide birth cohort in Japan, 238 mothers of infants with CL/P [186 children born with cleft lip (CL ± P) and 52 born with isolated cleft palate (CP)] were included in the analyses. The prospective association of children with CL/P and maternal self-harm ideation, which were acquired using item #10 in the Edinburgh Postpartum Depression Scale at 1 and 6 months postpartum, was examined using binomial logistic regression analyses after multiple imputations and with adjustments for several maternal (age at delivery, smoking habit, and alcohol intake) and child-related (sex and prevalence of other congenital diseases) variables.ResultsThe prevalence of self-harm ideation in 238 mothers of infants with CL/P at 1 and 6 months were 14.7% (35/238) and 18.8% (45/238) [8.2% (8,185/100,062) and 12.9% (12,875/100,062) in the control group], respectively. The odds ratio (95% confidence interval) for maternal self-harm ideation increased with CL/P prevalence [1.80 (1.22–2.65) and 1.47 (0.98–2.18)] at 1 and 6 months of age, respectively. After stratified by the prevalence of cleft lip, we found significant differences in the CL ± P group but not in the CP group. Furthermore, persistent self-harming ideation was associated with a higher risk in the CL ± P group [2.36 (1.43–3.89)].ConclusionCL/P, particularly cleft lip, which is more noticeable externally, was associated with an increased prevalence of maternal self-harm ideation. The findings in this study indicate some potential benefits of increasing support for mothers who have infants with CL/P.